57.6k views
5 votes
Solve the equation
33=12r-3(9-r)

User Luiscrjr
by
4.7k points

2 Answers

4 votes

Answer:

r = 4

Explanation:

User Dgorur
by
5.1k points
4 votes

Answer:

r = 4

Explanation:

Our goal is to let the r alone on one side of the equation.

33 = 12r-3(9-r)

First, let's distribute the 3 into the parenthesis:

33 = 12r - 3*9 - 3*(-r)

33 = 12r - 27 + 3r

Now we add 27 on both sides of the equation

33 + 27 = 12r - 27 + 3r + 27

60 = 12r + 3r

Now that we only have terms with r on the right side, we can sum them

60 = 15r

We divide by 15 on both sides

60/15 = 15r/15

4 = r

User David Basarab
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.